2021
DOI: 10.3390/ijerph18083856
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Children to Unhealthy Food and Beverage Advertisements in South Africa

Abstract: Television (TV) is a powerful medium for marketing food and beverages. Food and beverage marketers tend to use this medium to target children with the hope that children will in turn influence their families’ food choices. No study has assessed the compliance of TV marketers with the South African Marketing to Children pledge since the enactment of the 2014 food advertising recommendations by the South African Department of Health and the Advertising Standards Authority. This study investigated the extent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 23 publications
1
30
3
Order By: Relevance
“…The average frequency was higher in the other three countries compared to the published results from 22 countries [3] and in some recent studies [40].…”
Section: Accepted Manuscriptcontrasting
confidence: 60%
“…The average frequency was higher in the other three countries compared to the published results from 22 countries [3] and in some recent studies [40].…”
Section: Accepted Manuscriptcontrasting
confidence: 60%
“…42,43 Child directed marketing of unhealthy foods and beverages, in violation of South African law regulating fair marketing practices in relation to infant and young child food products, is another example of concerning marketing practices. 44,45 Beyond children, marketing of unhealthy food and beverages have also been shown to target vulnerable socio-economic classes. For example, a study reporting on marketing practices found that food producers target advertisements of starchy food to poorer black South Africans.…”
Section: Manufactured Demandmentioning
confidence: 99%
“…Manufacturers market or advertise their products using media outlets such as television, radio, print, and internet. 14 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%